Efforts To Increase The Locally Generated Revenue of Palembang: Access To Incentives And Investment - Flambonita, Suci; Samawati, Putu; Ahmaturrahman, Ahmaturrahman (Universitas Islam Negeri Raden Fatah Palembang, 2023)
Regional Original Revenue (PAD) is income obtained by the region, collected based on Regional Regulations by statutory regulations that are sourced from regional taxes, regional levies, separated regional wealth management results, and others including one the incentives and investment. as a measure to stimulate economic growth. If examined based on discussions with the four commissions, they approved the 2022 APBD of the Palembang City Government of IDR 3.84 trillion with a target of IDR 1.07 trillion of Original Regional Revenue (PAD). Efforts to increase investment must be supported by the development of quality infrastructure, professional apparatus, and the bureaucratic system as well as a safe and peaceful condition of the city of Palembang. The method used in this research is empirical with a statutory approach. Using the tools of analytical prescriptive analysis. To increase Regional Original Income (PAD) there are 2 (two) social implications that can be enjoyed by the region. First, the investment provides opportunities for potential economic resources to be processed into real economic forces that can encourage local economic dynamics, which in the end will also lead to economic growth and improvement of community welfare. Second, the investment will be followed by economic activities that can create new job opportunities. The availability of new jobs will certainly increase people's income and encourage the realization of prosperity and reduce poverty.